My Wildest Dream: A Letter to My Black Son - Lockhart, Lakisha R. (Religious education, 2020)
This article is a letter to my son. In this letter I tell him the truth of my reality in theological education, as one filled with sexism, racism, and various other experiences. I express my fears for him in this world as a black boy who will grow into a black man. I also discuss my hope for his future and the future of theological education. I discuss how I believe that playing, changing the rules, and having good friends to play with could aid in creating a better future not only for him but theological education as well.